Antioxidative and renoprotective effects of residue polysaccharides from Flammulina velutipes. (1st August 2016) - Lin, Lin; Cui, Fangyuan; Zhang, Jianjun; Gao, Xia; Zhou, Meng; Xu, Nuo; Zhao, Huajie; Liu, Min; Zhang, Chen; Jia, Le
Highlights: Three residue polysaccharides by Flammulina velutipes residue were extracted. The antioxidant and renoprotective effects of RPS were investigated. Galactose was the vital monosaccharide in maintaining the physiological status. Findings demonstrated that RPS had potential effects in functional foods. Abstract: Three extractable polysaccharides including Ac-RPS, Al-RPS and En-RPS were extracted from the residue of Flammulina velutipes and their antioxidative and renoprotective effects on STZ-induced mice were investigated. Biochemical and antioxidant analysis showed that the En-RPS had potential effects in decreasing the serum levels of CRE, BUN, ALB and GLU significantly, increasing the renal activities of SOD, CAT and GSH-Px remarkably, and reducing the renal contents of MDA prominently. Furthermore, the histopathological observations also displayed that En-RPS could alleviate kidney damage. These results demonstrated that En-RPS extracted from the residue of F. velutipes possessed potent antioxidant activities, and could be used as a promising therapeutic agent for inhibiting the progression of diabetic nephropathy. In addition, the monosaccharide compositions of these three RPS were also analyzed.